Processing of the Terminal Alpha-1,2-Linked Mannose Residues From Oligomannosidic N-Glycans Is Critical for Proper Root Growth - Veit, Christiane; König, Julia; Altmann, Friedrich; Strasser, Richard (Frontiers in Plant Science, 2018)
N-glycosylation is an essential protein modification that plays roles in many diverse biological processes including protein folding, quality control and protein interactions. Despite recent advances in characterization of the N-glycosylation and N-glycan processing machinery our understanding of N-glycosylation related processes in plant development is limited. In Arabidopsis thaliana, failure of mannose trimming from oligomannosidic N-glycans in the endoplasmic reticulum (ER) and cis/medial-Golgi leads to a defect in root development in the mns123 triple mutant. Here, we show that the severe root phenotype of mns123 is restored in asparagine-linked glycosylation (ALG)-deficient plants with distinct defects in the biosynthesis of the lipid-linked oligosaccharide precursor. The root growth of these ALG-deficient plants is not affected by the alpha-mannosidase inhibitor kifunensine. Genetic evidence shows that the defect is uncoupled from the glycan-dependent ER-associated degradation (ERAD) pathway that removes misfolded glycoproteins with oligomannosidic N-glycans from the ER. Restoration of mannose trimming using a trans-Golgi targeted alpha-mannosidase suppresses the defect of mns123 roots. These data suggest that processing of terminal mannose residues from oligomannosidic N-glycans is important for an unknown late-Golgi or post-Golgi process that is implicated in proper root formation.